Spread to the The Progression of Art as Western Learning East ——Wu Dayu's Artistic Discourse and Aesthetic Education (Journal of Global Arts Studies, 2024)
Background: In the grand historical context of the eastward spread of Western learning, the collision and blending of eastern and Western cultures have injected new vitality and challenges into the development of modern Chinese art. Objective: Discusses Wu Dayu's unique artistic practice path and aesthetic education theory system as an outstanding representative of the transition period of modern Chinese art. Methods: Through in-depth analysis of Wu Dayu's life path, and reveal his artistic ideas under the pattern of Western learning in the east. Results: In the cultural exchanges between China and the West in the 20th century, Wu Dayu not only introduced modern western art, but also made outstanding contributions to the revival of traditional Chinese art, further deepening the creation of modern Chinese art. Conclusion: As the core elements in the development of modern Chinese art, Wu Dayu's artistic discourse and aesthetic education view have great academic and practical significance for understanding the evolution of Chinese art history, stimulating contemporary art innovation and promoting the sustainable development of art.
Keywords: Wu Dayu; Western Learning Spreads to The East; Artistic Discourse; Educate People With Beauty